Landscape approaches to the evolution of the Byzantine/Medieval village-community in Greece - Vionis, Athanasios K. (Journal of Greek Archaeology, 2020)
The Greek landscape preserves a wide diversity of settlements of different character, which were established or developed especially during the later Post-Medieval and Early Modern periods (17th–19th centuries). Early studies in Post-Medieval and traditional rural settlements, with specific reference to Greece, have made a distinction between permanent and temporary ones. Temporary agricultural and pastoral settlements usually comprised 40–50 καλύβια or seasonal habitations, while permanent ones comprised clustered villages and hamlets of a compact or loose layout, such as the çiftlik or commercial farm estates. These rural settlement types appeared in mainland Greece in the 17th–18th centuries, and were used for the production of cash-crops to feed the growing demand for raw materials by rising industrial and capitalist states in Western Europe. Thus, past studies have primarily focused on the general appearance of rural settlements, on the economic forces that shaped their history in pre-modern Greece (and Cyprus), or, more recently, on aspects of their abandonment and post-abandonment formation processes and material change.